STEP on connected classroom climate in a hybrid learning environment. (2018) - Xu, Juan; Yang, Harrison Hao; MacLeod, Jason
This study provides a best-practice model for addressing the connectedness of a hybrid classroom and explores the effectiveness of connected classroom climate from the students-to-student perspective. Based on the connected classroom climate inventory, research findings suggest the connected classroom climate in hybrid classrooms can be equal to or greater than traditional face-to-face classrooms. Course implementation is discussed and recommendations for design characteristics are proposed for elevating student connectedness in hybrid classroom contexts.